Challenges and Solutions for Musculoskeletal Disorders in Athletes - Giovanni Iolascon; Umberto Tarantino; Antimo Moretti (Medicina, 2022)
The etymology of the word “athlete” derives from the ancient Greek ἀθλητής (athletés, from âthlos that is, fight, competition) [...]